What's in a "welcome survey"? Designing a course welcome survey as introduction to research methods in Communication. Issue 2 (3rd April 2021) - Levin, Allyson Volinsky
Abstract : Courses: Quantitative research methods, research methods, basic communication courses. Objectives: The goals of the exercise are for students (1) collaboratively to design a "real world" survey questionnaire, (2) to analyze survey questions and survey design to address if and how the survey meets its goals and (3) to evaluate the strengths and limitations of the welcome survey and of survey methods more broadly, and (4) for the instructor to collect information about students to promote learning throughout the course.